Treatment with Caffeic Acid and Resveratrol Alleviates Oxidative Stress Induced Neurotoxicity in Cell and Drosophila Models of Spinocerebellar Ataxia Type3 - Wu, Yu-Ling (Sci Rep, 2017)
Spinocerebellar ataxia type 3 (SCA3) is caused by the expansion of a polyglutamine (polyQ) repeat in the protein ataxin-3 which is involved in susceptibility to mild oxidative stress induced neuronal death. Here we show that caffeic acid (CA) and resveratrol (Res) decreased reactive oxygen species (ROS), mutant ataxin-3 and apoptosis and increased autophagy in the pro-oxidant tert-butyl hydroperoxide (tBH)-treated SK-N-SH-MJD78 cells containing mutant ataxin-3. Furthermore, CA and Res improved survival and locomotor activity and decreased mutant ataxin-3 and ROS levels in tBH-treated SCA3 Drosophila. CA and Res also altered p53 and nuclear factor-κB (NF-κB) activation and expression in tBH-treated cell and fly models of SCA3, respectively. Blockade of NF-κB activation annulled the protective effects of CA and Res on apoptosis, ROS, and p53 activation in tBH-treated SK-N-SH-MJD78 cells, which suggests the importance of restoring NF-κB activity by CA and Res. Our findings suggest that CA and Res may be useful in the management of oxidative stress induced neuronal apoptosis in SCA3.